Cybernetics, semiotics and meaning in the cinema - Keyan Tomaselli (Communicare)
THIS paper builds on Gene Youngblood's use of cybernetic theory in film analysis. It combines the cybernetic method with Peircian-derived semiotics in an attempt to derive a meta-theory of social process and film textual structure. An attempt is made to resolve the more deterministic elements of Youngblood's theory, developing a more probabilistic approach. The paper ends with some conjecture on how the cyber- semiotic theory developed can be combined with Lacanian psychoanalysis and Marxist approaches developed by the scholars contributing to the British journal Screen.